2017
DOI: 10.1016/j.piutam.2017.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and Carbon Nanotube Hybrid Structure: A Review

Abstract: Graphene has been reported with record-breaking properties which have opened up huge potential applications. Considerable amount of researches have been devoted to manipulate or modify the properties of graphene to target a more smart nanoscale device. Graphene and carbon nanotube hybrid structure (GNHS) is one of the promising graphene derivatives. The synthesis process and the mechanical properties are essential for the GNHS based devices. Therefore, this review will summarize the recent progress of the high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 41 publications
0
29
0
2
Order By: Relevance
“…DWCNT is considered as a special type of MWCNT wherein only two rolled up graphene sheets are present. MWCNT consists of two or more numbers of rolled-up concentric graphene sheets [22]. The diameter of SWCNT is generally up to 2 nm.…”
Section: Introductionmentioning
confidence: 99%
“…DWCNT is considered as a special type of MWCNT wherein only two rolled up graphene sheets are present. MWCNT consists of two or more numbers of rolled-up concentric graphene sheets [22]. The diameter of SWCNT is generally up to 2 nm.…”
Section: Introductionmentioning
confidence: 99%
“…This method combined the advantages of the high aspect ratio of CNTs and the high specific surface area provided by graphene. Experimental results showed that when CNTs were seamlessly attached to a graphene lattice, the as‐prepared 3D composite possessed enhanced electrical properties and electrochemical stability and modified mechanical and thermal properties . Interestingly, previous production of graphene‐CNT hybrid nanomaterials has relied on chemical vapor deposition (CVD) methods, which are obviously not very efficient with respect to yield or cost.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Currently, a new composite material based on two-dimensional graphene and one-dimensional carbon nanotubes (CNTs) is of great interest to this study [1][2][3][4][5][6]. There are several structural varieties of this composite material, each differing in their methods of joining a CNT and graphene, as well as their mutual orientation [7].…”
Section: Introductionmentioning
confidence: 99%